Association of Sleep Duration With All- and Major-Cause Mortality Among Adults in Japan, China, Singapore, and Korea - Svensson T; Saito E; Svensson AK; Melander O; Orho-Melander M; Mimura M; Rahman S; Sawada N; Koh W-P; Shu X-O; Tsuji I; Kanemura S; et al. (American Medical Association)
IMPORTANCE: The association between long sleep duration and mortality appears stronger in East Asian populations than in North American or European populations. OBJECTIVES: To assess the sex-specific association between sleep duration and all-cause and major-cause mortality in a pooled longitudinal cohort and to stratify the association by age and body mass index. DESIGN, SETTING, AND PARTICIPANTS: This cohort study of individual-level data from 9 cohorts in the Asia Cohort Consortium was performed from January 1, 1984, to December 31, 2002. The final population included participants from Japan, China, Singapore, and Korea. Mean (SD) follow-up time was 14.0 (5.0) years for men and 13.4 (5.3) years for women. Data analysis was performed from August 1, 2018, to May 31, 2021. EXPOSURES: Self-reported sleep duration, with 7 hours as the reference category. MAIN OUTCOMES AND MEASURES: Mortality, including deaths from all causes, cardiovascular disease, cancer, and other causes. Sex-specific hazard ratios (HRs) and 95% CIs were estimated using Cox proportional hazards regression with shared frailty models adjusted for age and the key self-reported covariates of marital status, body mass index, smoking status, alcohol consumption, physical activity, history of diabetes and hypertension, and menopausal status (for women). RESULTS: For 322 721 participants (mean [SD] age, 54.5 [9.2] years; 178 542 [55.3%] female), 19 419 deaths occurred among men (mean [SD] age of men, 53.6 [9.0] years) and 13 768 deaths among women (mean [SD] age of women, 55.3 [9.2] years). A sleep duration of 7 hours was the nadir for associations with all-cause, cardiovascular disease, and other-cause mortality in both men and women, whereas 8 hours was the mode sleep duration among men and the second most common sleep duration among women. The association between sleep duration and all-cause mortality was J-shaped for both men and women. The greatest association for all-cause mortality was with sleep durations of 10 hours or longer for both men (hazard ratio [HR], 1.34; 95% CI, 1.26-1.44) and women (HR, 1.48; 95% CI, 1.36-1.61). Sex was a significant modifier of the association between sleep duration and mortality from cardiovascular disease (χ25 = 13.47, P = .02), cancer (χ25 = 16.04, P = .007), and other causes (χ25 = 12.79, P = .03). Age was a significant modifier of the associations among men only (all-cause mortality: χ25 = 41.49, P < .001; cancer: χ25 = 27.94, P < .001; other-cause mortality: χ25 = 24.51, P < .001). CONCLUSIONS AND RELEVANCE: The findings of this cohort study suggest that sleep duration is a behavioral risk factor for mortality in both men and women. Age was a modifier of the association between sleep duration in men but not in women. Sleep duration recommendations in these populations may need to be considered in the context of sex and age.